Dynamic thiol/disulfide homeostasis and effects of smoking on homeostasis parameters in patients with psoriasis. (2nd October 2017) - Emre, Selma; Demirseren, Duriye Deniz; Alisik, Murat; Aktas, Akin; Neselioglu, Salim; Erel, Ozcan
Abstract: Purpose : Recently, increased reactive oxygen species (ROS), reduced antioxidant capacity, and oxidative stress have been suggested in the pathogenesis of psoriasis. The aim of this study to evaluate the thiol/disulfide homeostasis in patients with psoriasis. Materials and methods : Ninety patients with psoriasis who did not receive any systemic treatment in the last six  months were included in the study. Seventy-six age and gender-matched healthy volunteers served as control group. Thiol/disulfide homeostasis was measured in venous blood samples obtained from patient and control groups. Results : Native thiol and total thiol levels were significantly higher in patients than in control group. When thiol/disulfide hemostasis parameters and clinical and demographic characteristics were compared, a negative correlation was detected between native thiol and total thiol with age. The levels of total thiols had also negative correlation with PASI and duration of the disease. When we divided the patients into smokers and non-smokers, native thiol and total thiol levels were significantly higher in smokers than in controls, whereas native thiol and total thiol levels were comparable in non-smoker patients and controls. Conclusions : Thiol/disulfide balance shifted towards thiol in psoriasis patients and this may be responsible for increased keratinocyte proliferation in the pathogenesis of psoriasis.